Acoustic Sensor for Nitrox Gas Analysis and Monitoring - Stevens, C (2012)
Current practice in both sport and commercial diving promotes the use of oxygen enriched air 'Nitrox' to reduce risk of decompression injuries. Most gas analyzers used to prepare and monitor these gas concentrations utilize electrogalvanic (EG) cells which require repeated calibration, are highly moisture sensitive and have a limited lifespan. Here we report the design, construction, and evaluation of a new sensor based on the acoustic properties of different Nitrox mixtures. This sensor has no consumable chemicals, works well in all humidity levels and responds more quickly than EG cells. © 2012 IEEE.